PENGARUH KOMPETENSI KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PAGILARAN BATANG - Nancy Regita Aksa Panrelli, 15.05.52.0267; Murdianto, Agus (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of competence, compensation, and work discipline on employee performance. The object in this study is employees who work at PT. Stems. Sampling is done by using Simple Random Sampling technique and the number of samples is 120 respondents.The retrieval method is primary data using the questionnaire method by distributing a list of questions addressed by respondents at PT. Information to get information. Data analysis using validity test, reliability test, regression analysis, multiple regression analysis.The results of this study indicate that (1) Competence has a positive and significant effect on employee performance, (2) Compensation has a negative and not significant effect on employee performance, (3) Work discipline has a positive and significant effect on employee performance.